PERANCANGAN SISTEM INFORMASI PERTANIAN KABUPATEN TOBA BERBASIS WEB - Sianipar, Abriando Mangapul; Simamora, Roni J.; Lumbantoruan, Gortap (Universitas Methodist Indonesia, 2023)
Agricultural information systems are very important and very influential in conveying information about agriculture to the wider community. At this time information about agriculture in Toba district does not yet have the right system for conveying agricultural information, resulting in information about agriculture not being conveyed to the wider community, especially the people of Toba district properly and quickly. To overcome the above problems, the researchers designed a web-based agricultural information system in Toba district which aims to make it easier for the wider community to find the latest information about agriculture such as types of agricultural products, production yields, prices and agricultural activities in Toba district. This information system was built by utilizing the HTML, CSS and MySQL programming languages to process the database used to use the Sublime Text application as a place for program design.